Green Cosmetics to Environmental Sustainability - Purwanti, Lilik; Nasyi’ah, Eny Zuhrotin; Ibrahim, Melinda; Prakoso, Aryo (Universitas Swadaya Gunung Jati, 2024)
CSR is a business commitment to behavior ethically, operate legally and contribute to economic development while improving the quality of life of employees and their families, as well as local communities and society in general. One form of implementation of CSR activities has been carried out by The Body Shop in Indonesia with the Bring Back Our Bottle (BBOB) CSR Program. This research aims to analyze the corporate social responsibility program bring back our bottle the body shop. This research uses the literature study method. The main source of literature used in the analysis comes from the google scholar data base. The review of 17 relevant articles shows that The Body Shop has successfully integrated CSR programs into its core business strategy, with BBOB as one of the flagship programs. The program not only contributes to the reduction of plastic waste, but also raises consumer awareness about sustainable consumption. This program is in line with the concept of creating shared value. The Body Shop successfully creates shared value for both the company and society. Despite facing challenges such as the logistics of collecting and processing used packaging, the program has had a positive impact on The Body Shop's brand image as a socially and environmentally responsible company. The analysis shows that the success of the program is supported by several factors, including the company's long-term commitment to sustainability values, active engagement of consumers, and cooperation with local partners in the recycling process. This study provides valuable insights into the practical implementation of CSR in the cosmetics retail industry and can serve as a reference for other companies looking to develop similar CSR programs.